The Good, the Bad and the Ugly: Social Costs and Benefits of Female Migration on Filipino Families - Jamon, Grace Gorospe (Review of Women's Studies; Vol 19 No 1-2 (2009): Review of Women's Studies Volume XIX, Numbers 1-2 (January-December 2009), 2023)
This study is a contribution towards the research on the circumstances of those left behind and how their lives have been affected in complex ways by the departure of parents of migrant families. It will revisit the experiences and explore the social impact, the benefits and costs of the increasing number of female overseas Filipino workers (OFWs) on the family. More specifically, it will attempt to describe and analyze: 1) the problems brought about by distance among family members and how this affects the exercise of parental authority over children as well as marital relations between the spouses and how each of the family members cope; 2) the reproductive health and rights of the spouses; and 3) the economic status and social mobility of the family members. It will attempt to distill the main findings and insights from earlier empirical studies done on the same. Additional empirical data has been generated for this research from field interviews and focused group discussions (FGDs) conducted in Bataan Christian School in Balanga, Bataan.